تجربة ماليزيا في حوكمة المؤسسات المالية الإسلامية: دراسة تحليلية: Malaysia’s Experience in the Governance of Islamic Financial Institutions: An Analytical Study - Anwarul Haq, Amiri; Ghalia, Bouhedda (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2024)
ملخص البحث يهدف هذا البحث إلى دراسة تطور حوكمة المؤسسات المالية الإسلامية في ماليزيا، وتحليل الدور الذي يلعبه المجلس الاستشاري الشرعي في تعزيز هذه الحوكمة. يستعرض البحث الجذور التاريخية لتطور المصرفية الإسلامية في ماليزيا، مع التركيز على التأثيرات الناتجة عن اعتماد معيار الحوكمة الشرعية لعام 2019. ويعتمد البحث على المنهج الوصفي التحليلي بتحليل الجوانب التاريخية والتنظيمية ومعيار الحوكمة الشرعية لعام 2019، واستخلاص الدروس المستفادة من التجربة الماليزية لتطبيقها في سياقات دولية أخرى، مثل أفغانستان. أظهرت النتائج أن الإرادة السياسية القوية، والنهج التدريجي، والتركيز على التعليم، والالتزام بالحوكمة الشرعية، هي العوامل الرئيسية التي ساهمت في نجاح التجربة الماليزية. في ضوء هذه النتائج، توصي الدراسة بتبني الحكومات، وخاصة في أفغانستان، نهجًا تدريجيًا ومتكاملاً لتطوير النظام المالي الإسلامي، مع التركيز على التعليم، الشفافية، والابتكار في المنتجات المالية بما يتوافق مع الشريعة الإسلامية. Abstract This research aims to study the development of governance in Islamic financial institutions in Malaysia and analyze the role of the Shariah Advisory Council in enhancing this governance. The research reviews the historical roots of the development of Islamic banking in Malaysia, with a focus on the effects of adopting the Shariah Governance Standard of 2019. The study uses a descriptive-analytical approach by analyzing historical and regulatory aspects, as well as the Shariah Governance Standard of 2019, and deriving lessons learned from the Malaysian experience for application in other international contexts, such as Afghanistan. The results show that strong political will, a gradual approach, a focus on education, and adherence to Shariah governance are the main factors contributing to the success of the Malaysian experience. In light of these findings, the study recommends that governments, particularly in Afghanistan, adopt a gradual and integrated approach to developing the Islamic financial system, with an emphasis on education, transparency, and innovation in financial products that comply with Islamic law.